2019
DOI: 10.1155/2019/5872347
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephaly Analysis Supported by Computerized Tomography and Nuclear Magnetic Resonance

Abstract: Hydrocephalus is widely known as “hydrocephaly” or “water in the brain,” a building up of abnormal cerebrospinal fluid in the brain ventricles. Due to this abnormality, the size of the head becomes larger and increases the pressure in the skull. This pressure compresses the brain and causes damage to the brain. Identification by imaging techniques on the hydrocephalus is mandatory to treat the disease. Various methods and equipment have been used to image the hydrocephalus. Among them, computerized tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…13,14 Hydrocephalus was determined according to the triad of hydrocephalus proposed by Zhang et al, including the presence of widening of the anterior horn in a round or convex shape, dilatation of the posterior temporal horn, and the presence of periventricular hypodense. 15 Based on the type of hydrocephalus listed in the table, the communicating type was much more than non-communicating hydrocephalus or the blockage above the IV ventricle. A study conducted by Harwood also found that 30% of non-communicating hydrocephalus subjects.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Hydrocephalus was determined according to the triad of hydrocephalus proposed by Zhang et al, including the presence of widening of the anterior horn in a round or convex shape, dilatation of the posterior temporal horn, and the presence of periventricular hypodense. 15 Based on the type of hydrocephalus listed in the table, the communicating type was much more than non-communicating hydrocephalus or the blockage above the IV ventricle. A study conducted by Harwood also found that 30% of non-communicating hydrocephalus subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital hydrocephalus (HC) arises from an imbalance in cerebrospinal fluid (CSF) dynamics, resulting in increased CSF volume, influenced by ventricle and subarachnoid space dimensions [1]. Common causes of infant hydrocephaly encompass congenital malformations, intraventricular hemorrhages, neoplasms, infections, and age-specific factors [2]. At present, diagnosing fetal hydrocephalus involves intrauterine ultrasound, genetic testing, or postnatal assessment based on clinical signs, utilizing sonography, computed tomography (CT) scan, and/or magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…At present, diagnosing fetal hydrocephalus involves intrauterine ultrasound, genetic testing, or postnatal assessment based on clinical signs, utilizing sonography, computed tomography (CT) scan, and/or magnetic resonance imaging (MRI). CT and MRI become crucial for evaluating disease progression and management efficacy, as prenatal ultrasound cannot gauge intracranial pressure [1,2,3]. While hydrocephalus as a standalone condition is common, its co-occurrence with ulcerative colitis is exceptionally rare, warranting specialized attention due to the potential shared pathophysiology between the two conditions.…”
Section: Introductionmentioning
confidence: 99%
“…En la mayoría de los casos se asoció a edema transependimario. 11 Todos los pacientes fueron tratados con shunt que presentaban mecanismo "anti-siphon". Las presiones fueron medidas en milímetros de agua (mmH20).…”
unclassified